Transvenous Lead Extraction in a European Low-Volume Center without On-Site Surgical Support - Mohamed Dardari; Corneliu Iorgulescu; Vlad Bataila; Alexandru Deaconu; Eliza Cinteza; Radu Vatasescu; Paul Padovani; Corina Maria Vasile; Maria Dorobantu (Reports, 2023)
Indications for cardiac implantable electronic devices (CIEDs) are increasing. Almost one-third of device-related infections are endocarditis. Transvenous lead extraction (TLE) has emerged as an effective and safe approach for treating device-related infections and complications. Multiple types of extraction tools are being used worldwide. Our goal is to evaluate the safety and effectiveness of TLE using non-powered extraction tools. The study included patients between October 2018 and July 2022 requiring TLE according to EHRA expert consensus recommendations on lead extraction. A total of 88 consecutive patients were included. Indications for TLE included device-related infections in 74% of the patients. Of those, 32% had device-related endocarditis with or without sepsis. Staphylococcus Aureus was the most frequent pathogen in patients with endocarditis and positive bacteremia, and 57% had negative bloodstream cultures. A total of 150 cardiac pacing and defibrillator leads were targeted for extraction. The mean dwell time for leads was 6.92 ± 4.4 years; 52.8% were older than 5 years, 15.8% were older than ten years, and the longest lead dwell time was 26 years. Patients’ age varied between 18 and 98, with a mean age of 66 ± 16 years. Sixty-seven percent of patients were males. Using only non-powered extraction tools, we report 93.3% complete lead removal and 99% clinical success with partial extraction. We report no procedure-related death nor major complications. Minor complication incidence was 6.8%, and all complications resolved spontaneously. The 30-day mortality rate was 3.4%. TLE using non-powered extraction tools is safe and effective even without surgical backup on site.